The Correlation Between Elsa Speak and Student Listening Achievement at Senior High School - Firmansyah, Ardi; Setiyawan, Arisandi; Yuliawati, Fitrah (Institut Agama Islam Negeri Palopo, 2025)
This study aims to examine the relationship between the use of the Elsa Speak application and the listening achievement of class XI IPA students at MA Al-Djufri, involving 26 students. Data collection was carried out using a questionnaire and test, which showed that students obtained an average score of 89.62 after using the application. The results of the study showed a significant positive correlation, with a correlation coefficient of 0.670, which indicates that regular use of the Elsa Speak application can improve listening achievement. This shows that the application plays an important role in improving students' listening achievement, which confirms a strong relationship between the use of the application and students' listening achievement.